Omitting radiation therapy after lumpectomy for pure DCIS does not reduce the risk of salvage mastectomy. (February 2018) - Rakovitch, Eileen; Nofech-Mozes, Sharon; Hanna, Wedad; Sutradhar, Rinku; Gu, Sumei; Fong, Cindy; Tuck, Alan; Youngson, Bruce; Miller, Naomi; Done, Susan J.; Chang, Martin C.; Sengupta, Sandip; et al.
Abstract: Purpose: Radiation therapy (RT) after breast-conserving surgery (BCS) for Ductal Carcinoma in Situ (DCIS) halves the risk of local recurrence (LR). The omission of RT is often supported by the paradigm that patients who develop LR can be salvaged with further breast-conserving therapy leading to higher rates of breast preservation and improved quality of life. However, population-based, long-term rates of breast preservation in women treated by upfront BCS ± RT are unknown. Methods and materials: Women diagnosed with pure DCIS from 1994 to 2003 treated with BCS ± RT in Ontario were identified. Median follow-up is 12 years. The development and treatment of LR and contralateral breast cancers were determined by administrative databases with validation. The 10-year mastectomy-free survival was calculated using the Kaplan-Meier method. The impact of RT on breast preservation was determined by propensity-adjusted cox proportional hazards model. Results: The cohort includes 3303 women with DCIS; 1649 (50%) underwent BCS alone, 1654 (50%) underwent BCS + RT. Women treated by BCS alone were more likely to develop a LR compared to those treated by upfront BCS + RT (20.8% versus 15.5%, p < 0.001). Mastectomy was used to treat LR in 57.4% (197/343) of women who recurred after BCS alone and 67.6% (174/257) of those who recurred after BCS + RT. Women treated with upfront BCS + RT had higher rates of bilateral breast preservation at 10 years compared to those treated by BCS alone (87.3% vs.82.7%, p = 0.0096). Conclusion: Local Recurrence after BCS alone does not favor breast preservation. Highlights: Bilateral breast preservation is an important determinant of quality of life for women with DCIS. The management of LR and the long-term rates of breast preservation are unclear. We report the treatment of local recurrence in a population of women treated conservatively for DCIS. Women treated with RT have a greater rate of bilateral preservation compared to those treated by BCS alone.